Using μ2rheology to quantify rheological properties during repeated reversible phase transitions of soft matter. Issue 12 (26th May 2017) - Wehrman, Matthew D.; Milstrey, Melissa J.; Lindberg, Seth; Schultz, Kelly M.
Abstract : A novel microfluidic design enables repeated phase transitions in a single sample by surrounding fluid exchange and microrheological characterization. Abstract : A microfluidic device is designed to measure repeated phase transitions, gelation and degradation, on a single sample by exchanging the surrounding fluid while minimizing shear stress. This device enables quantitative microrheological characterization of material properties over multiple phase transitions, determining whether the material returns to the same equilibrium state. Fluid exchange is accomplished by using a two layer design, the sample is trapped in the first layer and the second layer is a well for the exchanging fluid. Fluid enters the sample chamber symmetrically creating equal pressure around the sample, trapping it in place. Multiple particle tracking (MPT) microrheology, a passive microrheological technique, measures the dynamic rheological properties during each phase transition. Combining rheological characterization and sample manipulation using microfluidics is termed μ 2 rheology. The utility of this technique is demonstrated by characterizing several phase transitions of a fibrous colloidal gel, hydrogenated castor oil. Gelation and degradation is induced by an osmotic pressure gradient created by contact with a glycerine based gelling agent and water, respectively. Several transitions are measured using a single sample. Nine transitions, five gel–sol and four sol–gel, are the maximum number of transitions characterized in a single sample. This microfluidic device and measurement technique is widely applicable and can be easily adapted to any system where solvent exchange is used to induce a change in material properties.